Nueva localidad y características de la población de Acer skutchii Rehder en la Sierra de Manantlán, Jalisco, México - Jardel Pelaez, Enrique J.; Cuevas Guzman, Ramon; Santiago P., Ana Luisa; Muñoz M., M. Elizabeth; Aragon David, Jose (Instituto de Ecología, A.C., 1996)
A new locality of Acer skutchii Rehder was registered in the cloud forest of the Sierra de Manantlán, Jalisco, Mexico. This study provides a description of its population structure and floristic associates.